Engineering Characteristics and Application Analysis of Red Sandstone in the Lanzhou Metro - Yujie Li; Zhongju Feng; Yanpeng Zhu; Pengyun Wei; Fudeng Zhao (Geofluids)
The water-rich red sandstone strata at the Lanzhou Metro site area have special engineering properties and vary greatly in their speed of disintegration when exposed to water. There is an urgent need for a comprehensive and systematic study of the engineering properties of red sandstone and their classification. From the disintegration speed of red sandstone encountered during the excavation of Lanzhou metro lines 1 and 2, the relationship between physical parameters such as particle size, composition, dry density, and permeability coefficient as well as mechanical parameters such as shear wave speed, dynamic penetration test (DPT), natural uniaxial compressive strength, and disintegration speed of red sandstone was analyzed through indoor and outdoor tests and geological exploration data statistics, and classification guidelines for red sandstone are given. The results show a significant correlation between dry density, permeability coefficient, natural uniaxial compressive strength, and disintegration speed. The red sandstone can be classified as I, II, and III according to the disintegration speed, dry density, permeability coefficient, and natural uniaxial compressive strength. The design of the foundations is differentiated according to the classification, and different support systems are used for the deep foundation pits of the metro stations. The category I red sandstone pit is supported by diaphragm walls with internal bracing, the category II pit by bite piles with internal bracing, and the category III pit by row piles with internal bracing. The study results can provide technical support and experience reference for the investigation, design, and construction of metro projects in similar red sandstone distribution areas.